Amoxicillin-induced bacterial gut dysbiosis decreases IL-1β and IL-6 expression but exacerbate lung inflammatory response against Mycobacterium bovis—Bacille Calmette-Guérin (BCG) - Tatimara M. Miyauchi-Tavares; Evandro Neves Silva; Joyce Alves dos Santos; Priscila V. Sousa; Marcos F. Teodoro Braga; Caroline M. Carminatti; Victoria B. Lanza; Bruna C. Fagundes; Rômulo Dias Novaes; Leonardo Augusto de Almeida; Patrícia Paiva Corsetti (PLoS ONE, 2025)
Tuberculosis is one of the leading causes of global mortality, and the standard, prolonged, and intensive treatment can affect intestinal homeostasis. This study investigated amoxicillin-induced bacterial gut dysbiosis and its impact on the immune response of C57BL/6 mice to pulmonary infection by Mycobacterium bovis—BCG. It was observed that amoxicillin treatment resulted in bacterial gut dysbiosis, characterized by an increase in the phylum Proteobacteria and a reduction in Bacteroidetes and Firmicutes. This alteration was associated with a decrease in the animals’ body weight and a reduction in the expression of pro-inflammatory cytokines such as IL-1β and IL-6, suggesting a compromised immune response. Additionally, microstructural analysis revealed significant alterations in the caecum and pulmonary structure of the mice, indicating tissue damage associated with intestinal dysbiosis. The results indicate that amoxicillin-induced bacterial gut dysbiosis may negatively affect pulmonary immunity and exacerbate M. bovis-BCG infection, highlighting the need to consider the impacts of intestinal microbiota on the development and control of tuberculosis. This study contributes to the understanding of the interaction between intestinal microbiota, antibiotic treatment, and immunity in pulmonary infections.